Family legacy and leadership : preserving true family wealth in challenging times - Daniell, Mark Haynes , 1955-; Hamilton, Sara S. (Wiley finance, 2010)
To date, there is no book specifically tailored to this highly lucrative market on the subject of leadership of a wealthy family